Electrical properties of La-Mn-codoped BaTiO3-(Bi0.5Na0.5)TiO3 lead-free PTCR ceramics. Issue 21 (1st November 2021) - Leng, Senlin; Cheng, Hao; Zhang, Renhui; Gao, Caiyun; Li, Zhicheng
Abstract: La-Mn-codoped 0.97BaTiO3 -0.03(Bi0.5 Na0.5 )TiO3 ceramics (abbreviated as x La- y Mn-BBNT3, x  = 0.001, 0.002, 0.003, 0.004; y  = 0, 0.0005, 0.001, 0.0015, 0.002) for application of lead-free positive temperature coefficient of resistivity (PTCR) thermistors were prepared using a wet chemical route. The analysis of XRD patterns shows that all prepared powders and ceramics are composed of pure tetragonal perovskite phase. The x  = 0.002 La-doped ceramic sintered in air has a Curie temperature of Tc about 140 °C, room-temperature resistivity (ρ25 ) of ~10 3  Ω cm and resistivity jump (log(ρmax /ρmin )) of ~3 orders in magnitude. It is also found that the resistivity jump of prepared ceramic reaches up to 4.4 orders in magnitude when y  = 0.0015 Mn was doped. Influence of grain and grain-boundary effect on PTCR effect was analyzed by complex impedance spectra measured at different temperatures, and the results reveal that the grain boundary effect plays key role in the PTCR effect.